2007
DOI: 10.1038/nsmb1313
|View full text |Cite
|
Sign up to set email alerts
|

The structure-specific endonuclease Mus81 contributes to replication restart by generating double-strand DNA breaks

Abstract: Faithful duplication of the genome requires structure-specific endonucleases such as the RuvABC complex in Escherichia coli. These enzymes help to resolve problems at replication forks that have been disrupted by DNA damage in the template. Much less is known about the identities of these enzymes in mammalian cells. Mus81 is the catalytic component of a eukaryotic structure-specific endonuclease that preferentially cleaves branched DNA substrates reminiscent of replication and recombination intermediates. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
363
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 348 publications
(387 citation statements)
references
References 49 publications
16
363
3
Order By: Relevance
“…However, the precise substrate recognized by MUS81 at the fork is not known, but possibilities include Holliday junctions generated by replication fork regression or the stalled fork itself 8,21,22 . Our data on the role of MUS81 in the response to HU are in agreement with Hanada et al 6 with regard to MUS81-induced DNA DSB formation. Yet, Hanada et al 6 found that genetic ablation of MUS81 led to HU-sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the precise substrate recognized by MUS81 at the fork is not known, but possibilities include Holliday junctions generated by replication fork regression or the stalled fork itself 8,21,22 . Our data on the role of MUS81 in the response to HU are in agreement with Hanada et al 6 with regard to MUS81-induced DNA DSB formation. Yet, Hanada et al 6 found that genetic ablation of MUS81 led to HU-sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…We found that DNA DSB formation was evident after treatment for 24 h as evidenced by pulsed-field gel electrophoresis (PFGE) that detects DNA breaks (Fig. 1c), a finding that is in agreement with a number of previous studies 6,15 . Furthermore, treatment with HU led to checkpoint activation at the time of DNA DSB accumulation, including robust ATM activation and the phosphorylation of key downstream targets like CtIP and CHK2 (Fig.…”
Section: Fbh1supporting
confidence: 92%
See 3 more Smart Citations